RESPON DAN MINAT BELI PRODUK BUSANA (STUDI KASUS PADA FOLLOWERS INSTAGRAM TOKO GRIYA TULUNGAGUNG - Luthfiyani, Mimma; Nurohman, Dede (LPPM Institut Pendidikan Nusantara Global, 2023)
Digital marketing is an important marketing strategy used by UMKM actors in dealing with the impact of the Covid-19 pandemic. Instagram social media is one of the most widely used platforms, especially for business actors engaged in the fashion sector, including GriyaAlika. The success of a marketing strategy through Instagram is determined by the number of followers. This paper aims to map the responses of followers of the instagram account too griya alika on buying interest. This study uses a qualitative descriptive method with an netnograpdi approach. This study found that the response of netizens to the marketing content carried out by Griya Alika with the @griyaalika account had a high enough enthusiasm for Instagram posts, resulting in many comments and likes showing interest or buying interest.